Examining the effectiveness of boot camps: a randomized experiment with a long-term follow up - Bottcher, Jean (Journal of research in crime and delinquency, 2005)
The boot camp model became a correctional panacea for juvenile offenders during the early 1990s, promising the best of both worldsαless recidivism and lower operating costs. Although there have been numerous studies of boot camp programs since that time, most have relied on non randomized comparison groups. The California Youth Authority's CYA's experimental study of its juvenile boot camp and intensive parole program called LEADαversus standard custody and paroleαwas an important exception, but its legislatively mandated in-house evaluation was prepared before complete outcome data were available. The present study capitalizes on full and relatively long-term follow-up arrest data for the LEAD evaluation provided by the California Department of Justice in August 2002. Using both survival models and negative binomial regression models, the results indicate that there were no significant differences between groups in terms of time to first arrest or average arrest frequency. ABSTRACT FROM AUTHOR